Peran Kepala Sekolah dalam Manajemen Berbasis Sekolah Kajian Perspektif Kepemimpinan Kristen (Pascasarjana IAKN Manado, 2021)
This study aims to examine perspective of Christian leadership on the role of principals in school-based management. By using qualitative literature research methods and the source of the data is secondary data, this research is done by data analyzing, classifying and organizing the data that is sorted for later presented and concluded. Data acquisition contains the concepts of Christian leadership, school-based management implementation, and the role of the principal in school-based management. The results of the literature review are (1) theoretically, the principal requirements of Christian leadership's vocation, where according to the qualifications and competencies a person has can be determined to be the school leader, (2) practically, above theory's conformity is not intensive applied to every task and role elements, attitudes and behaviors, as well as the principal's competence. (3) the inhibiting factor of the principal's role is not in line with Christian leadership is due to work orientation that is too broad, but does not equip themselves, while the supporters are activities in the form of training, direction, and competency development that focus on the overall task and function in educational leadership.